Advances in accounting behavioral research. Vol. 23 - Karim, Khondkar E. (Emerald Publishing Limited, 2020)
Advances in Accounting Behavioral Research promotes research across all areas of accounting, incorporating theory from, and contributing knowledge to, the fields of applied psychology, sociology, management science, ethics and economics. Focusing on research that examines both individual and organizational behavior relative to accounting, the series provides a unique opportunity for the exchange of peer reviewed knowledge across all areas of accounting behavioral research and the development, discussion and expansion of theories from psychology, sociology and related disciplines. Advances in Accounting Behavioral Research encourages research that tests theory, explains theory, and develops theory that can be applied to better understand accounting domains. Accordingly, reviews of established theory and how that theory has and could be used in accounting are also strongly encouraged.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Accounting -- Research; Management -- Research; Psychology, Applied; Business & Economics -- Accounting -- Managerial; Management accounting & bookkeeping